KEMAMPUAN PEMAHAMAN KONSEP BANGUN RUANG DITINJAU DARI MOTIVASI BELAJAR - Mumtazah, Maulidah Rafa; Triyana, Illah Winiati (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2025)
This research is motivated by the low level of mathematical conceptual understanding of Indonesian students in the topic of spatial geometry, where learning motivation is identified as a crucial influencing factor. The focus of this research is to analyze and describe in depth the ability of seventh grade students to understand the concept of spatial geometry, viewed from three different levels of learning motivation: high, medium, and low. As a crucial step, this study uses a descriptive qualitative approach, in which three students were selected as subjects through purposive sampling based on the results of a motivation questionnaire. Data were collected through conceptual understanding tests, in-depth interviews, and observations, then analyzed using the Miles and Huberman model. The main findings show a clear correlation between the level of motivation and the depth of understanding: highly motivated students were able to meet all indicators, moderately motivated students showed weaknesses in the application of procedures, while low motivated students had very limited understanding. In conclusion, learning motivation fundamentally influences the quality of cognitive engagement and the depth of students' mathematical conceptual understanding, emphasizing the importance of learning strategies that can build intrinsic motivation. ABSTRAKPenelitian ini dilatarbelakangi oleh rendahnya pemahaman konsep matematis siswa Indonesia pada materi bangun ruang, di mana motivasi belajar diidentifikasi sebagai salah satu faktor pengaruh yang krusial. Fokus penelitian ini adalah untuk menganalisis dan mendeskripsikan secara mendalam kemampuan pemahaman konsep bangun ruang siswa kelas VII, ditinjau dari tiga tingkatan motivasi belajar yang berbeda: tinggi, sedang, dan rendah. Sebagai langkah penting, penelitian ini menggunakan pendekatan kualitatif deskriptif, di mana tiga siswa dipilih sebagai subjek melalui purposive sampling berdasarkan hasil angket motivasi. Data dikumpulkan melalui tes pemahaman konsep, wawancara mendalam, dan observasi, kemudian dianalisis dengan model Miles dan Huberman. Temuan utama menunjukkan adanya korelasi yang jelas antara tingkat motivasi dengan kedalaman pemahaman: siswa bermotivasi tinggi mampu memenuhi seluruh indikator, siswa bermotivasi sedang menunjukkan kelemahan pada aplikasi prosedur, sementara siswa bermotivasi rendah memiliki pemahaman yang sangat terbatas. Kesimpulannya, motivasi belajar secara fundamental memengaruhi kualitas keterlibatan kognitif dan kedalaman pemahaman konsep matematis siswa, menegaskan pentingnya strategi pembelajaran yang mampu membangun motivasi intrinsik.